Advancing Aggregation‐Induced Emission‐Derived Biomaterials in Viral, Tuberculosis, and Fungal Infectious Diseases - Wei Wang; Junjie Wang; Ziwei Hu; Xiaowei Yan; Qiuxia Gao; Xiaoxue Li; Judun Zheng; Bin Li; Yunxia Wu; Yuhui Liao (Aggregate)
ABSTRACT Contagious diseases caused by different types of highly contagious pathogens, such as SARS‐CoV‐2, monkeypox virus, Mycobacterium tuberculosis, and human immunodeficiency virus, could trigger global outbreaks and bring a huge public health burden. Advanced diagnostic, therapeutic, and preventive strategies are urgently needed to deal with the epidemic of contagious diseases. Aggregation‐induced emission (AIE) has emerged as one of the promising candidates that exhibit tunable photophysical properties, high biocompatibility, exceptional photostability, and a distinguishing aggregation‐enhanced fluorescence. As a result, they offer effective strategies for the diagnosis, treatment, and prevention of contagious diseases. This review systematically outlined the latest research progress of AIE‐based biomaterials and mechanisms in contagious diseases. The versatility of AIE molecules, as well as highly efficient fluorescence properties, has the potential to offer innovative strategies to combat these health challenges. Thanks to recent advances in materials science and a better understanding of aggregation‐induced emission luminogens (AIEgens), AIEgens have great potential to provide better solutions for the treatment, detection, and prevention of contagious diseases. By reviewing state‐of‐the‐art methods for the killing, detection, and prevention of contagious agents and highlighting promising technological developments, this outlook aims to promote the development of new means for the prevention and control of emerging, re‐emerging, and major contagious diseases as well as further research and development activities in this critical area of research.